2017
DOI: 10.1007/s11136-017-1563-z
|View full text |Cite
|
Sign up to set email alerts
|

What contributes to long-term quality of life in breast cancer patients who are undergoing surgery? Results of a multidimensional study

Abstract: The results show that the timely detection and proper management of psychological distress and the enhancement of posttraumatic growth are of great value, as they might be important contributing factors to long-term quality of life in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 65 publications
1
11
2
1
Order By: Relevance
“…Advances in breast cancer detection and treatment have meant that many more women are entering survivorship, with the 5-year survival rate now almost 90% for Western countries. 1,2 Consequently, much research has focused on improving quality of life (QOL) in breast cancer survivors in the long term, 3 including gaining a greater understanding of the woman's broader interpersonal context and intimate relationships. 1,[4][5][6] Many un-partnered women report a strong desire to begin romantically "dating" (ie, meeting with someone with whom they have a romantic interest) following breast cancer treatment, in the hope of forming a new relationship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in breast cancer detection and treatment have meant that many more women are entering survivorship, with the 5-year survival rate now almost 90% for Western countries. 1,2 Consequently, much research has focused on improving quality of life (QOL) in breast cancer survivors in the long term, 3 including gaining a greater understanding of the woman's broader interpersonal context and intimate relationships. 1,[4][5][6] Many un-partnered women report a strong desire to begin romantically "dating" (ie, meeting with someone with whom they have a romantic interest) following breast cancer treatment, in the hope of forming a new relationship.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Moreover, breast cancer survivors face significant and unique changes to physical appearance, which is important given the central role of attraction and appearance in romantic dating. 19 Given the limited research available, the first aim of the current study was to explore differences between partnered and un-partnered breast cancer survivors who were interested in romantic dating, in terms of (1) dating-related anxiety, (2) interpersonal competence, (3) body image factors (self-evaluative salience, motivational salience, body satisfaction), and (4) self-compassion. The second aim was to investigate factors associated with dating anxiety and interpersonal competence skills in un-partnered breast cancer survivors who were interested in dating.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding pain and tightness, Verbelen et al [3] reported that at 2 years after surgery, rates of tightness accompanied by pain and numbness associated with shoulder dysfunction ranged from 5 to 50%. In addition, because Naaman et al [10] reported that reduction in anxiety (in terms of illness and future life) and alleviation of depression improved QOL of breast cancer surgery patients and Wittmann et al [12] reported that postoperative HRQOL involves physical distress, anxiety, and depression, anxiety was thus used as an indicator of a change in the patients' psychological state.…”
Section: -2 Investigationmentioning
confidence: 99%
“…Leach et al [11] reported that a 24-week exercise intervention improved HRQOL and depression, and Wittmann et al [12] reported that postoperative HRQOL involves physical pain, anxiety, and depression. Gordon et al [13] found that an 8-month exercise intervention was effective in improving HRQOL and cost-effectiveness.…”
mentioning
confidence: 99%
“…PROs comprise various aspects of the subjectively perceived state of health from the patient's point of view, such as HRQoL, satisfaction with care, and drug adherence [9,15,16]. With regard to the therapy setting, monitoring HRQoL and the occurrence of symptoms appears to be of particular relevance, primarily during therapy, but also as a long-term follow-up for improving and supporting patients´ well-being [17][18][19][20]. The importance of measuring PRO in breast cancer patients is also stated in the German S3-guideline [21].…”
Section: Patient-reported Outcomes and Health-related Quality Of Lifementioning
confidence: 99%